Trisomy X and myelodysplastic syndrome (MDS) with eosinophilia - Mohd Tohit, Eusni Rahayu; Leong, Chooi Fun; Shuib, Salwati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
We reported a young patient with myelodysplastic syndrome (MDS) with eosinophilia, in which her chromosomal analysis revealed the presence of trisomy X and a marker chromosome at chromosome 11. The technique used to detect the chromosomal abnormalities is a multicoloured –fluorescent in situ hybridization technique (M-FISH). Our observation suggested that these underlying chromosomal abnormalities were probably responsible for her development of MDS with eosinophilia. Myelodysplastic syndrome (MDS) is a condition whereby there is ineffective production of haematopoietic stem cells and poor quality of cells produced. The cause can either be a primary bone marrow problem, de novo or therapy related. Most MDS cases are secondary rather than primary. Many chromosomal abnormalities have been found in cases of myelodysplastic syndrome. We described a case of MDS with eosinophilia in association with presence of trisomy X and a marker chromosome in chromosome 11.